Toward a Du Boisian Framework of Immigrant Incorporation: Racialized Contexts, Relational Identities, and Muslim American Collective Action. (12th April 2021) - Yazdiha, Hajar
Abstract: Answering longstanding questions about the relationship between immigrant identity, collective action, and societal incorporation requires a dynamic theory that integrates these micro, meso, and macro levels of analysis. I propose a Du Boisian framework of immigrant incorporation that centers immigrants' subjectivities, accounting for variation in immigrants' perceptions of their relational social positions and subsequent strategies for shifting these positions. In this conceptualization of collective identity and collective action, macro-contexts enable and constrain collective identities through the process of ethnoracial formation, but immigrants negotiate competing perceptions of these identities and the political context, shaping divergent strategies to negotiate group position. I illustrate this framework by drawing on focus groups with Muslim American immigrants, identifying three central couplings of perceived identity and collective action strategy: 1) a perception of an integrating, "model citizen" collective identity that is aspirationally white, shaping assimilationist strategies for incorporation; 2) a perception of temporarily stigmatized identity with corresponding "identity-improvement" strategies for incorporation; and 3) a perception of racialized identity that rejects aspirational whiteness coupled with coalition-building with Black and Brown communities to target racialized systems altogether. Following Du Bois' legacy, this framework expands our understanding of the dialectic between macro-contexts and micro-dynamics in immigrant incorporation and builds upon growing research that questions whether the quest for societal inclusion is necessarily a process of integration into the dominant category.